Cryptocurrencies Advantages and Disadvantages: A Review - Shadi Khaled Zakarneh; Zaer Qaroush; Ammar Dawabsheh (International Journal of Applied Sciences and Smart Technologies, 2022)
Abstract. With the rapid spread of technology in all sectors of life and the necessary need to increase the speed of payment processes, confidentiality, and privacy in business operations, cryptocurrencies appeared. The cryptocurrency is a virtual and intangible currency, in which transactions are made through the Internet and without any physical exchange between parties. These currencies are characterized by decentralization, transparency, privacy. Because transactions are carried out through a cryptography process and depend on Blockchain technology it is highly protected. Blockchain generally is a distributed ledger or a decentralized database. The Blockchain architecture combines advanced cryptography, distributed consensus mechanisms, and a complex system of incentives and rewards. In cryptocurrency, transactions are created, transferred, and verified through an integrated process called mining. Network members (network nodes) who carry out verification processes of transactions are called miners. As it is a credit or debit card used in banking transactions, in cryptocurrencies there is a so-called electronic wallet that is used for transactions that take place on cryptocurrencies over the Internet through computers or smartphones. Blockchain technology architecture has given cryptocurrencies many advantages and features that increase its strength and distinction from regular currencies and regular financial transactions such as decentralization, high confidentiality, anonymity, speed of transactions, very low fees, unlimited number of transactions, unrestricted by geography and borders, transparency, protection from Inflation, and the peer-to-peer network. The misuse of powerful features in cryptocurrencies and Blockchain technology has led to many disadvantages such as the risks of lack of knowledge, the lack of wide acceptance, the high risk of investing in them, its volatile nature, and the inability to return missing payments. This study concentrates on cryptocurrencies in terms of advantages and disadvantages.